Heat Loss Prevention Education Aids Nurses' Knowledge in Prevention of Hypothermia in Newborns. (30th November 2017) - Purnamasari, Meivita Dewi; Rustina, Yeni; Waluyanti, Fajar Tri
ABSTRACT: Newborns are at risk of developing hypothermia due to the instability of their thermoregulation systems and inability to adjust to changes in ambient temperature. This risk increases during hospitalization. Education is a strategy to improve nurses' understanding of the prevention of hypothermia in newborns in the hospital. This study aimed to analyze the impact of education about preventing heat loss on nurses' knowledge and behavior in preventing hypothermia in newborns. The study design was a quasi-experiment with one group pre-test–post-test and a total sample of 21 neonatal nurses who were selected using the consecutive sampling method. The results indicated that there was significant difference in nurses' knowledge and behavior pre- and post-education intervention ( p  < .001; α = .05). This study suggests that education on prevention of heat loss is an effective strategy to promote nurses' knowledge and behavior in preventing hypothermia.